Design of Compact Trapezoidal Bow-Tie Chipless RFID Tag - Lei Xu; Kama Huang (International Journal of Antennas and Propagation)
This paper presents a novel compact design of a low cost fully printable slot-loaded bowtie chipless RFID tag. The tag consists of two trapezoidal metallic patches loaded with multiple slot resonators. Slots with similar size or adjacent frequencies are loaded alternately on two bow-tie patches to double the number of data bits within the UWB frequency band without increasing the mutual coupling between slots. A coding capacity of 12 bits is obtained with 12 slots within a reasonable size of 35 mm × 33 mm. RCS of the tag has been given by simulation. Measurements have been done using a bistatic radar configuration in the frequency domain and transmission coefficient is measured. The agreement between the simulation and measurement validates this new concept of design. This tag has high data capacity and low cost and can be directly printed on product such as personal ID, credit cards, paper, and textile because it needs only one conductive layer.